Validation of the Chinese version of the self-injurious thoughts and behaviors interview for adolescent outpatients in Taiwan: a cross-sectional study - Hui-Chun Huang; Yu-Hsin Huang; Hui-Ching Liu; Chiu-Rong Huang; Ming-Ru Sung; Fang-Ju Sun; Shen-Ing Liu (Scientific Reports, 2025)
Abstract The Self-Injurious Thoughts and Behavior Interview (SITBI) has been widely used in Western countries, but its use in Chinese culture is limited. Based on the scarcity of standardized Chinese interviews to assess self-injurious thoughts and behaviors, this study aimed to validate the SITBI Chinese version (SITBI-C). The psychometric properties of the SITBI-C were tested in 195 outpatient adolescents with various levels of suicidality. The test-retest, interrater and concurrent validity were investigated in this study. The analysis of the SITBI-C showed perfect test-retest reliability within one week. The interrater agreement was also excellent, ranging across SITB-C items. The validity indices were good when comparing the responses to the SITBI-C and other interview-based and self-reported measures, suggesting strong convergent validity. Overall, the results of this research suggested that the SITBI-C demonstrated good psychometric properties. The SITBI-C is appropriate for assessing suicidality in the Chinese adolescent population and can be used to assess adolescent suicidal ideation to determine the risk for suicidal behavior.